Kekuatan Eksekutorial Dalam Pelaksanaan Eksekusi Putusan Badan Arbitrase Nasional Indonesia; Studi Kasus Putusan Badan Arbitrase Nasional Indonesia Jakarta No.801/II/ARB-BANI/2016 - Dara Fitryalita; Asep Syarifuddin Hidayat; Mufidah Mufidah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:The presence of the Indonesian National Arbitration Board (BANI) provides new hope in effective and efficient dispute resolution efforts. Nevertheless, BANI has obstacles when carrying out the execution of the decision. This study uses normative juridical methods and literature studies. The results showed that the BANI decision No. 801 / II / ARB-BANI / 2016 had the power of execution because the BANI had registered an authentic copy of the arbitration award at the Registrar of the South Jakarta District Court, so that the decision could be carried out with court assistance or voluntarily by the respondent. However, the implementation encountered an obstacle namely the removal of the object of achievement because of public policy. Other potential obstacles include the applicant's execution and execution refusing because it is not in accordance with the ruling, other than because the ruling decision is considered unclear, the execution of movable property, the existence of resistance, and payment assets are difficult to find.Keywords: Executorial Strength, Arbitration, Decision of the Indonesian National Arbitration Board